Quality assurance of uncured polymer matrix prepregs through the application of non-destructive methods. (January 2023) - Pollock, Luke; O'Byrne, Sean; Wild, Graham
Abstract: The Airbus A350 is 53% composite, primarily Hexcel prepreg, making uncured polymer matrix prepregs a key material in aerospace applications. Non-Destructive Testing and Evaluation (NDT&E) of prepregs is essential for Quality Assurance (QA) purposes during manufacturing. Following an introduction to fibre reinforced polymers, this study reports current and evolving technologies such as automated tape laying, automated fibre placement, and out-of-autoclave prepregs. Sources of variations in quality of prepregs are identified to highlight the need to ensure their quality as structural materials. The technologies that may be employed to ensure the quality of prepreg materials is broken into the three main life cycle stages prior to curing: manufacturing, storage, and lay-up. These stages are further sub-classified dependent upon the methodologies and technologies applied for QA. A final discussion is given regarding the future trends of NDT&E QA for prepreg materials including the potential use of digital twin and machine learning technologies for future aerospace systems.